2014
DOI: 10.1186/1471-2334-14-256
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the cervical cancer screening program in women living with HIV in Denmark: comparison with the general population

Abstract: BackgroundWomen living with HIV (WLWH) are at increased risk of invasive cervical cancer (ICC). International HIV guidelines suggest cervical screening twice the first year after HIV diagnosis and thereafter annually. Adherence to the HIV cervical screening program in Denmark is unknown.MethodsWe studied women from a population-based, nationwide HIV cohort in Denmark and a cohort of age-matched females from the general population. Screening behaviour was assessed from 1999–2010. Adjusted odds ratios (OR’s) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 27 publications
3
23
2
Order By: Relevance
“…This suggests that women who are in care for longer periods might have a better understanding of the necessity of gynaecological supervision and be more willing to return to the HIV clinic for IGC. A recent Danish populational study showed comparable results, with CD4 count > 350 cells/μL and HIV RNA < 500 copies/mL being predictors of attendance at the HIV cervical screening program [14]. In the Danish study only 2.6% of HIV positive women obtained the recommended two cervical cancer screenings in the first year from HIV diagnosis.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This suggests that women who are in care for longer periods might have a better understanding of the necessity of gynaecological supervision and be more willing to return to the HIV clinic for IGC. A recent Danish populational study showed comparable results, with CD4 count > 350 cells/μL and HIV RNA < 500 copies/mL being predictors of attendance at the HIV cervical screening program [14]. In the Danish study only 2.6% of HIV positive women obtained the recommended two cervical cancer screenings in the first year from HIV diagnosis.…”
Section: Discussionmentioning
confidence: 80%
“…However, data coming from observational studies in Europe, although scarce, shows that barriers to cervical cancer screening still exist, from both the patient's and the health system's perspectives [14,15,20]. It is important to note that according to a recently published EuroSIDA study of a pan-European longitudinal observational cohort, cancer screening has a low coverage in both Eastern and non-Eastern European countries [21].…”
Section: Discussionmentioning
confidence: 99%
“…A high proportion of WLWH included and not included in the study; 28.7 % and 52.5 %, had not been screened for CC in the preceding 3 to 5 years. We have previously assessed low screening attendance in this cohort of WLWH and support the idea of cytology as part of an annual medical HIV review, integration of HIV care and cervical screening in a single clinic setting and targeted public health messages aimed at health care professionals at HIV centres, general practitioners and WLWH [37]. However, the low screening attendance does not explain differences in cytological abnormalities between WLWH and WGP, since women were matched on prior screening history.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the direct effect of immunosuppression on invasive cancer risk is still debated [69][70][71] . Recent studies suggest that there is no increased risk of SCC in HIV-positive women when adherence to the strict cervical cancer screening programs is complete [72]. Accordingly, there is a need for improving awareness of the importance of cervical M A N U S C R I P T…”
Section: Hpv-associated Cervical Cancermentioning
confidence: 99%
“…12 cancer screening, that is still partial in the HIV+ women [72] and probably, even lower in female transplant patients.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%